(untitled) (Nordic Journal of African Studies, 2001)
This paper examines the roles of water in healing among traditional Yoruba healers in southwestern Nigeria. The data for the study derived from five focus group discussions (FGDs) conducted between April and June of 1998 and between November and December of 1999 at the Ile-Ife region, Osun state, Nigeria. Pluralistic health care services in Nigeria are discussed in light of modern, traditional and popular branches of medicine. Originating from the ancient tradition of the Yoruba, the various roles that water plays in traditional healing are discussed. Issues of interest include understanding illnesses and diseases as misfortunes, the various ways to prevent misfortunes in life, ways of using water when preparing remedies, and understanding how water actually heals in the therapeutic process. This is highlighted by an example of the baths, which are common treatments, especially for women suffering from infertility. The study suggests encouraging further cooperation between the modern health care services and the traditional practitioners in order to achieve better health.